Optimalisasi Diri Kaum Wanita Melalui Kreatifitas Membuat Boneka dari Kaos Kaki - Gea, Leniwan Darmawati; Kim, Doye; Atty, Sonya Debora; Yanti, Yanti (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
As humans, self-optimization is a demand that is naturally inherent in our existence. Self-optimization can be achieved through various things, and one of them is through self-development in craft creativity. This is a form of self-empowerment which contains benefits both for oneself and the wider community. It is in this regard that Community Service activities are carried out through the creation of making dolls from socks. This activity was carried out at STT ATI.The methods in this activity are lectures, discussions and exercises. The result of this training is that the participants are able to produce their handiwork optimally as a form of optimizing themselves as women.